PENGARUH ANGKATAN KERJA, KEMISKINAN DAN INFLASI TERHADAP PENGANGGURAN DI INDONESIA - Nadya Oktaviyani Marius (2021)
This study aims to determine the effect of the labir force, poverty and inflation on unemployment in Indonesia. This study uses time series 1991-2020, the sample data is 30 years. To see the effect of labor force, poverty an inflation the researcher used multiple linier regresssion analysis method with secondary data types. The form of the multiple linier regression equation is Y=β_0+β_1 X_1+β_2 X_2+β_3 X_3+ε. The result showed that the labor force variable had a significant effect on unemployment rate in a negative direction, this means that every one percent increae in the labor force level will cause the unemployment in Indonesia to decrese by -14.53419 percent. Poverty variable has a significant effect on unemployment rate in a negative direction, this mean that every one percent increase in the poverty rate will cause the unemployment in Indoneia to decrese by -0.149124 percent. Inflation variable has a significant effect on unemployment rate in positive direction, this means that every one percent inflation rate will cause unemployment in Indonesia to increase by 0.067686 percent. Keywords: labor force, poverty, inflation and unemployment